The Effect of Money Supply and Inflation on the Economic Growth of Lao PDR - Viphommavongsa, touny; ONLUESAY, Khamnouan; DUANGKEO, Vilany (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The study was conducted under topic the Effect of Money Supply and Inflation on the Economic Growth of Lao PDR. The objective of the study was to examine the effects of money supply (M2) and inflation (INF) on the economic growth of Lao PDR using annual time-series data from 1991 to 2023, covering a period of 33 years. Data was sourced from the Bank of the Lao PDR and the National Statistics Center. The analysis employed the STATA program as a tool to test the relationships between variables using the Vector Error Correction Model (VECM). Additionally, the study included Impulse Response Function (IRF) analysis and stability testing of the model using the CUSUM and CUSUMSQ methods. The results of the short-term and long-term relationships among variables using the VECM revealed that the economic growth rate of Lao PDR is significantly related to the growth rate of money supply (M2) and inflation (INF) in an inverse direction. This finding aligns with the established hypotheses Specifically, 1% increase in the growth rate of money supply (M2) leads to 48.46% decrease in the economic growth rate of Lao PDR. Similarly, 1% increase in the inflation rate (INF) results in 44.95% reduction in economic growth, both with a statistical confidence level of 99%. The test of the short-term relationship among variables showed that the coefficient of the Error Correction Term (ECT) was -0.0796141, indicating a negative value with 99% statistical confidence, suggesting that within a year, the economic growth rate (GDP) and other variables adjust by 7.96% towards the long-term equilibrium when deviating from it. Lastly, the stability test of the model using the CUSUM and CUSUMSQ methods indicated that the model remained stable throughout the study period.